Secretome of Paenibacillus sp. S-12 provides an insight about its survival and possible pathogenicity - Kumari, Kiran; Sharma, Parva Kumar; Ma, Ying; Singh, Rajnish Prakash (Folia microbiologica, 2023)
Our aim in this study was to characterize and investigate the secretome of Paenibacillus sp. S-12 by nanoLC-MS/MS tool-based analysis of trypsin digested culture supernatant proteins. Using a bioinformatics and combined approach of mass spectrometry, we identified 657 proteins in the secretome. Bioinformatic tools such as PREDLIPO, SecretomeP 2.0, SignalP 4.1, and PSORTb were used for the subcellular localization and categorization of secretome on basis of signal peptides. Among the identified proteins, more than 25% of the secretome proteins were associated with virulence proteins including flagellar, adherence, and immune modulators. Gene ontology analysis using Blast2GO tools categorized 60 proteins of the secretome into biological processes, cellular components, and molecular functions. KEGG pathway analysis identified the enzymes or proteins involved in various biosynthesis and degradation pathways. Functional analysis of secretomes reveals a large number of proteins involved in the uptake and exchange of nutrients, colonization, and chemotaxis. A good number of proteins were involved in survival and defense mechanism against oxidative stress, the production of toxins and antimicrobial compounds. The present study is the first report of the in-depth protein profiling of Paenibacillus bacterium. In summary, the current findings of Paenibacillus sp. S-12 secretome provide basic information to understand its survival and the possible pathogenic mechanism.
Keywords: Virulence; bakteriální proteiny; sekretom; tandemová hmotnostní spektrometrie; Paenibacillus; Bacterial Proteins; Secretome; faktory virulence; virulence; Tandem Mass Spectrometry; Virulence Factors